2020
DOI: 10.1007/s00234-020-02588-5
|View full text |Cite
|
Sign up to set email alerts
|

High-signal venous sinuses on MR angiography: discrimination between reversal of venous flow and arteriovenous shunting using arterial spin labeling

Abstract: Purpose It is sometimes difficult to differentiate between high signals originating from a reverse flow on magnetic resonance angiography (MRA) and occult arteriovenous shunting. We attempted to determine whether arterial spin labeling (ASL) can be used to discriminate reversal of venous flow from arteriovenous shunting for high-signal venous sinuses on MR angiography. Methods Two radiologists evaluated the signals of the venous sinus on MRA and ASL obtained from 364 cases without arteriovenous shunting. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(24 reference statements)
2
3
0
Order By: Relevance
“…A previous study reported that left-sided compression of the brachiocephalic vein and the absence of enlarged external carotid arteries can be the findings that cause jugular vein reflux [ 5 ]. Although our case matches the latter one, the other reports showed high specificity of hypersignal intensities in the cavernous sinus on ASL to differentiate DAVF from reversal flow [ 4 ]. Our case did not meet this finding.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A previous study reported that left-sided compression of the brachiocephalic vein and the absence of enlarged external carotid arteries can be the findings that cause jugular vein reflux [ 5 ]. Although our case matches the latter one, the other reports showed high specificity of hypersignal intensities in the cavernous sinus on ASL to differentiate DAVF from reversal flow [ 4 ]. Our case did not meet this finding.…”
Section: Discussionsupporting
confidence: 87%
“…Jugular vein reflux is occasionally observed in healthy patients [ 4 , 5 , 14 ], and some reports have described this phenomenon as mainly caused by compression of the left brachiocephalic vein and jugular valve dysfunction [ 5 , 6 ]. Although jugular valve dysfunction has been thought to be related to transient global amnesia [ 15 ], jugular venous reflux is usually detected incidentally in supine position MRI, and most cases are diagnosed incidentally or exhibit pulsatile tinnitus without severe symptoms [ 5 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] TOF-MRA is also available on clinical MRI scanners and is a completely noninvasive modality, but offers lower sensitivity than venous-ASL for the presence of DAVF. [ 2 , 9 ] In the present case, bilateral neuroophthalmic symptoms were worsened at 1 month after from SSSO. However, increased signal intensity in the left SOV had completely resolved and that in the right SOV remained to a slight extent despite the fact that TOF-MRA showed CSDAVF had been completely obliterated.…”
Section: Discussionsupporting
confidence: 46%
“…With reference to CSDAVF, Takahashi et al reported that the most fistulous points of CSDAVF were detected in the posterior portion of the cavernous sinus or in the posterior portion of the intercavernous sinus by contrast-enhanced MRI (12). Even though non-contrast MRA is shown to be reliable for the diagnosis of the cavernous fistula, potential misdiagnosis with benign jugular venous reflux can occur, which can be differentiated by careful radiological interpretation (13,14).…”
Section: Discussionmentioning
confidence: 99%